Analysis of Transcriptional and Metabolic Differences in the Petal Color Change Response to High-Temperature Stress in Various Chrysanthemum Genotypes - Zhimei Li; Hougao Zhou; Yan Chen; Minyi Chen; Yutong Yao; Honghui Luo; Qing Wu; Fenglan Wang; Yiwei Zhou (Agronomy)
Flower color is one of the most important ornamental traits of chrysanthemums. Previous studies have shown that high temperatures can cause the petals of some chrysanthemum varieties to fade; however, the molecular mechanisms behind this phenomenon remain poorly understood. This study examines the mechanisms of color change in purple chrysanthemums under high-temperature stress using combined metabolomic and transcriptomic analyses. Four chrysanthemum varieties—two heat-stable (‘Zi Feng Che’ and ‘Chrystal Regal’) and two heat-sensitive (‘Zi Hong Tuo Gui’ and ‘Zi Lian’)—were analyzed. High-temperature conditions (35 °C) significantly downregulated key anthocyanins in heat-sensitive varieties, particularly cyanidin-3-O-(3″,6″-O-dimalonyl)glucoside and pelargonidin-3-O-(3″,6″-O-dimalonyl)glucoside. Transcriptome analysis revealed differential gene expression involved in anthocyanin biosynthesis and degradation, with significant enrichment in the MAPK signaling, phenylpropanoid biosynthesis, flavonoid biosynthesis, and anthocyanin biosynthesis pathways. The study highlighted the differential expression of CHS, DFR, ANS, GT1, 3AT, and UGT75C1 genes in anthocyanin synthesis between heat-sensitive and heat-tolerant varieties. Compared to heat-stable varieties, the petals of heat-sensitive varieties exhibited greater differential expression of heat-responsive transcription factors, including HSFs, ERFs, MYBs, and WRKYs. Genes that show a significant negative correlation with the downregulated anthocyanins, including Cse_sc012959.1_g030.1 (βG), Cse_sc001798.1_g020.1 (MYB), Cse_sc006944.1_g010.1 (MYB), and Cse_sc000572.1_g090.1 (HSF), might regulate anthocyanin accumulation in chrysanthemums in response to high-temperature stress. These results provide guidance for the cultivation management and variety selection of chrysanthemums under high-temperature conditions. Additionally, they lay the foundation for elucidating the molecular mechanisms of flower color stability under heat stress and for breeding new heat-tolerant varieties.